If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + -1f + 9f + -1(f + -3) = f + f Reorder the terms: f + -1f + 9f + -1(-3 + f) = f + f f + -1f + 9f + (-3 * -1 + f * -1) = f + f f + -1f + 9f + (3 + -1f) = f + f Reorder the terms: 3 + f + -1f + 9f + -1f = f + f Combine like terms: f + -1f = 0 3 + 0 + 9f + -1f = f + f 3 + 9f + -1f = f + f Combine like terms: 9f + -1f = 8f 3 + 8f = f + f Combine like terms: f + f = 2f 3 + 8f = 2f Solving 3 + 8f = 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 3 + 8f + -2f = 2f + -2f Combine like terms: 8f + -2f = 6f 3 + 6f = 2f + -2f Combine like terms: 2f + -2f = 0 3 + 6f = 0 Add '-3' to each side of the equation. 3 + -3 + 6f = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 6f = 0 + -3 6f = 0 + -3 Combine like terms: 0 + -3 = -3 6f = -3 Divide each side by '6'. f = -0.5 Simplifying f = -0.5
| 4m-12m+(m-3)=2m | | 3x+14+2x-4=90 | | -2-5(r-2)=-3(1-2r) | | 156-5x=31x+20 | | .833333x-.2x+4=.7x | | 506-?=265 | | 7(2n-4)-5=-40+7n | | 4ln(x-4)=4 | | (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= |